Vulvovaginal candidiasis in Iranian women: Molecular identification and antifungal susceptibility pattern - Khaksar Baniasadi, Ali; Ayatollahi Mosavi, Seyyed Amin; Sharifi, Iraj; Bamorovat, Mehdi; Salari, Samira; Ahmadi, Atefeh; Amanizadeh, Azam; Agha Kuchak Afshari, Setareh (The journal of obstetrics and gynaecology research, 2022)
Aim Vulvovaginal candidiasis (VVC), is a common fungal infection that remains a global concern. The objectives of this study were molecular identification and assessment of the antifungal susceptibility profile of Candida species, causing VVC in southeast Iran. Methods A cross‐sectional investigation was carried out on 119 nonpregnant females suspected of VVC between February 2019 and May 2021. Yeast samples were characterized to the species level by conventional and molecular methods. All Candida isolates were examined for in vitro susceptibility profile to six conventional antifungal drugs using Clinical and Laboratory Standards Institute guidelines. Results Out of 119 subjects, 52 (43.7%) cases were affected by VVC, out of whom 11 (21.15%) cases had recurrent vulvovaginal candidiasis (RVVC). The species distribution was as follows; Candida albicans (n = 21; 40.4%), C. glabrata (n = 11; 21.2%), C. tropicalis (n = 9; 17.3%), C. parapsilosis (n = 5; 9.7%), C. africana (n = 3; 5.7%), C. famata (n = 1; 1.9%), C. lusitaniae (n = 1; 1.9%), and C. dubliniensis (n = 1; 1.9%). The resistance rate of Candida isolates to fluconazole, itraconazole, and voriconazole were 15.38%, 11.5%, and 3.8%, respectively. Resistance to fluconazole was obtained in 46% (5/11) of RVVC cases but only in 7% (3/41) of VVC cases. Conclusion This study demonstrated that the majority of VVC cases were caused by non‐albicans Candida species which also were resistant to some antifungal agents. Hence, our findings revealed the importance of conducting periodical epidemiological studies to determine changes in species distribution. Moreover, for effective management of treatment and infection, it is imperative to evaluate the susceptibility profiles of Candida species isolated from VVC patients.